Innovative Technologies for Studying the Impact of Climate Change on River Basins in the Guba-Khachmaz Region of Azerbaijan - Huseynova Gumru; Valiyeva Asmar; Tahmezli Elvira; Surkhayli Sanan; Tahmezli Matanat (BIO Web of Conferences)
It is believed that multivariate analysis for water quality management of Guba-Khachmaz economic region, which includes Shabran, Khachmaz, Guba, Gusar and Siyazan districts in the northeastern part of the Republic of Azerbaijan, will be more useful in terms of interpreting quality data. It is possible to prepare a large database for forecasting by integrating accurate results of spatial image analysis into the GIS database from time to time. The application of this approach is recommended in studying the current environmental situation of Guba-Khachmaz economic region of the Republic of Azerbaijan and in analyzing the current and expected impacts of climate change. The application of modern trends and technological innovations is the most effective method to combat and prevent this global crisis. As a result of the studies, it was determined that the most effective way to obtain, collect and analyze information on the impacts of climate change in the territory of the Republic of Azerbaijan, including Guba- Khachmaz economic region, is the use of Geographic Information Systems (GIS). The general monitoring framework was applied to analyze changes in climate characteristics in large regions at different time scales. The study further shows that online approaches such as GEE combined with remote sensing datasets are useful for monitoring climate change impacts, especially in semi-arid and arid regions, to model dynamic climate changes. In summary, the results of this study are of great importance to water resource planners and managers and make a significant contribution to the advancement of GIS science through the application and identification of effective methods for mapping climate change impacts on water resources.